Cochlear trajectory in pediatric patients. (27th October 2014) - Jackson, Neal M.; Givens, Victoria B.; Carpenter, Clelie C.; Allen, Laveil M.; Morrell, Brooke B.; Hurth, Charles; Arriaga, Moises A.; Ying, Yu‐Lan Mary; Arcement, Christopher; McCarter, Kevin S.; Jeyakumar, Anita
Abstract : Objectives/Hypothesis: As cochlear implantation increases, surgeons are noting possible anatomical differences in pediatric population. Outcome objectives were to study pediatric temporal bone anatomy using high‐resolution temporal bone imaging, and analyze the anatomical differences in group 1 (<12 months) versus group 2 (1–4 years) versus group 3 (5–10 years) versus group 4 (10–18 years). Study Design: Retrospective chart and radiologic review. Methods: A retrospective chart and radiologic review of pediatric patients undergoing high‐resolution computer tomography of the temporal bones from April 2001 to February 2013 was conducted. Scans were reviewed to record the transmastoid angle and transcanal angle. Results: Seven hundred fifty patients were identified. A total of 1, 426 ears were reviewed. The age range was 8 days to 21 years. Of the patients, 57.0% (n = 407) were male. The patients were divided into four groups: group 1 (<12 months), group 2 (1–4 years), group 3 (5–10 years), and group 4 (10–18 years). The transmastoid angle was observed to have variability. Significant differences were observed between groups 2 and 3 ( P  = .0028) and groups 2 and 4 ( P  = .0432). Analysis on the transcanal angle was performed. Significant differences existed between age groups 1 and 3 ( P  = .0150), groups 1 and 4 ( P  = .0038), and groups 2 and 4 ( P  = .0358). Conclusions: Considerable variation exists in pediatric temporal bones. The largest difference in the transmastoid angle was seen in children aged 1 to 4 years. The largest variability in the transcanal angle is between the infant (<12 months) and children >4 years of age. These differences are surgically relevant for round window identification and facial nerve safety during cochlear implant surgery in infants. Level of Evidence: 4 Laryngoscope, 125:961–965, 2015